Analysis of stock price movements based on reference prices and sales volume: a study at PT Bukit Asam Tbk - Muji Gunarto; Rini Wulansari (Program Studi Magister Manajemen FE Unsri, 2020)
The purpose of this study was to find out whether the movement of the share price of PT Bukit Asam Tbk (PTBA) occurred due to the impact of fluctuations in the Reference Coal Price (HBA) and coal sales volume (VP) or not. Taking HBA data from the publication of the Ministry of Energy and Mineral Resources (ESDM), PTBA coal sales volume is obtained from company financial reports and PTBA share price data is obtained from the Indonesia Stock Exchange (BEI) and Yahoo Finance. This study uses quarterly data from January 2009 to December 2018. All data are then analyzed using the VAR / VECM method. The results showed that the Impulse Response Function (IRF) HBA had a significant positive impact on PTBA's stock price in the short and long term. Meanwhile, coal sales volume had an insignificant positive impact on PTBA's share price. Forecast Variance Decompositions (FEVD) also shows that the response generated by the HBA is greater than the coal sales volume factor against the PTBA stock price during the observation period. From this research it can be concluded that the rise and fall of HBA and coal sales volume have clear implications for companies and investors. So it is recommended that companies always evaluate the performance and effectiveness of strategic policies. As for investors, it is useful as a source of investment information, in relation to portfolio strategies.